2014
DOI: 10.1109/temc.2013.2294958
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Conductor Surface Roughness Effects on Signal Propagation for Stripline Interconnects

Abstract: Conductors with a roughened surface have significant effects on high-speed signal propagation on backplane traces designed for a 10+ Gb/s network. An accurate approach to evaluate these effects, including the signal attenuation and the phase delay, is proposed in this paper. A differential extrapolation roughness measurement technique is first used to extract the dielectric properties of the substrate used for lamination, and then a periodic model is used to calculate an equivalent roughened conductor surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 18 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…The thickness of the conductor of trace and ground plane is t s = t g = 36 μm. The width of the ground is larger than the effective width w g ≈ 6h 1 . The roughness root mean square (RMS) Rq value of the roughness profile is 1.0 μm.…”
Section: Numerical Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The thickness of the conductor of trace and ground plane is t s = t g = 36 μm. The width of the ground is larger than the effective width w g ≈ 6h 1 . The roughness root mean square (RMS) Rq value of the roughness profile is 1.0 μm.…”
Section: Numerical Resultsmentioning
confidence: 92%
“…In high-speed planar transmission lines, the conductor surface roughness has a great influence on the conductor loss and phase velocity of the transmission lines. 1 By consequence, this roughness should be considered in the design in order to improve the electromagnetic reliability. At present, there are two existing approaches to model the conductor surface roughness impact on loss.…”
Section: Introductionmentioning
confidence: 99%
“…For the 4section Wilkinson power divider, the resistor loss reaches about 4.597%, but synchronously, the sum of the dielectric loss and the conductor loss is just about 1.353%. Nevertheless, the practical conductor loss will increase due to the additional loss that is brought by the surface roughness [8]. So the calculated results are just for the reference.…”
Section: The Loss Analysismentioning
confidence: 99%
“…Horn et al experimentally showed that there is a substantial effect on both transmission line insertion loss and velocity of propagation due to surface roughness in conductors [4]. Guo et al proposed an approach to evaluate the conductor surface roughness effects on signal propagation, including signal attenuation and phase-delay, where a periodic structure model has been proposed to calculate equivalent roughened conductor surface impedance [5].…”
Section: Introductionmentioning
confidence: 99%